Briefing: UK-RAS white paper in robotics and autonomous systems for resilient infrastructure. Issue 3 (27th October 2017) - Fuentes, Raul; Chapman, Timothy; Cook, Michael; Scanlan, Jim; Li, Zhibin; Richardson, Robert C
Abstract : This paper presents an extended briefing of the recently published UK-Robotics and autonomous systems (RAS) network Whie Paper in RAS for resilient infrastructure. It aims at setting out a vision of what RAS systems will be able to deliver in infrastructure, what are the current barriers and challenges to achieve that vision and what can the UK Government do to ensure that the UK remains at the forefront in this field.